An Assessment of the effectiveness of the use of e-learning in improving distant learning system and organizational development in Geography departments in colleges of education in Anambra state (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2025)
The rapid advancement of technology has significantly transformed educational systems worldwide, with e-learning emerging as a powerful tool in enhancing distance learning and organizational development. This study used a descriptive survey design to assess the effectiveness of e-learning in improving distance learning systems and organizational development in Geography departments of colleges of education in Anambra State. A sample of 107 respondents (lecturers and students) was selected through simple random sampling. Data were collected using a validated and reliable structured questionnaire, analyzed using descriptive statistics, correlation analysis, and ANOVA. Results showed moderate usage of e-learning platforms, with a mean ranging from (2.24) to (2.91). Organizational development strategies were moderately adopted, with a focus on professional development (mean = 3.35). E-learning moderately enhanced learning outcomes, with a mean ranging from (2.37) to (2.73). A moderate positive correlation (r = 0.471) was found between e-learning and organizational development. Hypotheses revealed significant differences influenced by factors like marital status and age group. However, the study also found inconsistent adoption across departments, suggesting that more strategic implementation is needed for maximum impact. This study provides evidence supporting the role of e-learning in enhancing both the educational and organizational dimensions of Geography departments in Anambra State, while also highlighting the need for further investment in infrastructure and faculty training to ensure more effective integration. The findings contribute to the understanding of e-learning’s potential to reshape teaching and organizational practices in higher education in Nigeria.
Keywords: e-learning, distant learning, organizational development, Geography departments, colleges of education, educational technology